2003
DOI: 10.1002/mpo.10335
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin nephrotoxicity affects magnesium and calcium metabolism

Abstract: Cisplatin is not directly toxic to bone, but cisplatin nephrotoxicity leading to magnesium wasting may affect magnesium and calcium metabolism, both of which contribute to bone integrity. The specificity of the magnesium lesion suggests that cisplatin may have an affinity for proteins that regulate magnesium absorption. Sulfhydryls such as amifostine can reduce the toxicity of cisplatin in adults, but current pediatric data do not indicate a role for sulfhydryl therapy to reduce cisplatin toxicity in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 38 publications
2
28
0
2
Order By: Relevance
“…Similary, the renal GSH level by WG or FBG pretreatment was increased higher than it of normal mice. Especially, FBG administration showed a significant increase (p<0.05) [34,35].…”
Section: Ros and Gsh Levels In Serum And Kidneymentioning
confidence: 93%
See 1 more Smart Citation
“…Similary, the renal GSH level by WG or FBG pretreatment was increased higher than it of normal mice. Especially, FBG administration showed a significant increase (p<0.05) [34,35].…”
Section: Ros and Gsh Levels In Serum And Kidneymentioning
confidence: 93%
“…NF-κB is a major proinflammatory transcriptional factor sequestered in the cytoplasm by the inhibitor protein IκBα. Phosphorylation of IκBα leads to the release of NF-κBand then NF-κB translocates to the nucleus and promotes the transcription of target genes including inflammatory mediators and cytokines such as COX-2, iNOS, TNF-α and IL-6 [35,37]. Figure 5 shows p-IκBα and NF-κBp65 protein expressions.…”
Section: Renal Oxidative and Inflammatory Protein Expressionsmentioning
confidence: 99%
“…Clinical and experimental studies have shown that CDDP interferes with magnesium transport, predominantly in the distal tubules [17][18][19]. Hypomagnesaemia caused by CDDP administration may persist for a few years after the end of therapy [20][21][22][23] and, in 1/3 to 2/3 children, may become permanent [21,24].…”
Section: Clinical Aspects Of Cisplatin Nephrotoxicitymentioning
confidence: 99%
“…CDDPrelated hypocalcaemia is resistant to equalisation with only calcium supplementation. The mechanism of hypocalcaemia secondary to hypomagnesaemia implies that normalisation of the calcium level may be achieved only through simultaneous magnesium and calcium substitution [20]. In addition to hypomagnesaemia and hypocalcaemia, patients may also present with hypokalaemia [25] and, very rarely, hyponatraemia (renal salt-wasting syndrome) [26,27].…”
Section: Clinical Aspects Of Cisplatin Nephrotoxicitymentioning
confidence: 99%
See 1 more Smart Citation